Role of a Teacher in Teaching Speaking by Following a Communicative Approach: To What Extent is this Possible in an ESL Context Like Bangladesh ? (Global Journal of Human-Social Science, 2016)
This paper is predominantlya short research which investigates the issue of how a teacher can promote the practice of speaking English by following a communicative approach within the traditional context of Bangladeshi language classrooms. The paper thus consists of four segments of literature reviews based on some secondary data collected from contemporary online journals and books. In a brief overview, it can be said that the paper starts with an assessment of the role of teachers in case of prioritizing fluency over accuracy in our language classrooms. This is followed by a discussion on the common sorts of speaking activities which an ESL teacher is ought to follow to promote fluent speaking within the classroom contexts. After this, the second last section focuses on some basic problems which act as hindrances in case of teaching speaking communicatively; for example the negative impact of Bangladesh's language based identity and its influence on teaching English Speaking. Lastly the paper sheds light on the controversial issue of whether it is even possible to teach speaking communicatively to our young school learners or not; and if so than to what extent is it actually possible.
Keywords: communicative approach; speaking activities; ESL speaking context; role of a teacher